2016
DOI: 10.1057/ejdr.2015.22
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory study of Dairying Intensification, Women’s Decision Making, and Time Use and Implications for Child Nutrition in Kenya

Abstract: Dairy intensification as a development strategy is expected to improve household nutrition, yet the pathways by which this occurs are not well understood. This article examines how women's time use and decision-making patterns related to dairy income and consumption are associated with dairy intensification, as a way of exploring the links between intensification and nutrition. Results from our mixed methods study conducted with households representing low, medium and high levels of dairy intensification in ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Dairy farming in Kenya is managed by both men and women and their orientations may influence the performance and dairy farming career resilience. However, there is dearth of empirical study on gendered differences on entrepreneurial orientation among dairy agripreneurs, despite the documented evidence of gender differences in running dairy business (Njuki et al, 2016).…”
Section: Gender and Entrepreneurial Orientationmentioning
confidence: 99%
See 2 more Smart Citations
“…Dairy farming in Kenya is managed by both men and women and their orientations may influence the performance and dairy farming career resilience. However, there is dearth of empirical study on gendered differences on entrepreneurial orientation among dairy agripreneurs, despite the documented evidence of gender differences in running dairy business (Njuki et al, 2016).…”
Section: Gender and Entrepreneurial Orientationmentioning
confidence: 99%
“…Another explanation can be attributed to the fact that, dairy industry needs good organization, management and time as compared to crop farming. Women being more precise in nature and present at home as compared to men, will play significant role in dairy enterprises hence take high risk in such investments (Njuki et al, 2016).…”
Section: Gendered Impact Of Agripreneurial Orientations On Agripreneumentioning
confidence: 99%
See 1 more Smart Citation
“…Inequities in these domains are present in the Kenyan dairy sector (Njuki et al, 2015). Recent literature reviews (Farnworth, 2015;Gallina, 2016;Katothya, 2017;Tavenner & Crane, 2016) show that gender roles and dynamics greatly influence the distribution of control and benefit in the Kenyan dairy sector.…”
Section: Gendered Contributions To the Farm Householdmentioning
confidence: 99%
“…As a result of these circumstances, individuals do not receive sufficient nutrient intakes to sustain optimal well-being. Some research has shown that it is not unusual to begin feeding children livestock-derived food (particularly milk) before 6 mo of age when they should be exclusively breastfeeding (Micere et al, 2016). With that said, recent surveys confirmed that almost 40% of children above 6 mo living in informal settlements in peri-urban Nairobi did not consume cow's milk daily.…”
Section: Introductionmentioning
confidence: 99%